Associations between vitamin D levels and depressive symptoms in healthy young adult women. Issue 1 (30th May 2015) - Kerr, David C.R.; Zava, David T.; Piper, Walter T.; Saturn, Sarina R.; Frei, Balz; Gombart, Adrian F.
Abstract: There have been few studies of whether vitamin D insufficiency is linked with depression in healthy young women despite women׳s high rates of both problems. Female undergraduates ( n =185) living in the Pacific Northwest during fall, winter, and spring academic terms completed the Center for Epidemiologic Studies Depression (CES-D) scale weekly for 4 weeks (W1–W5). We measured serum levels of vitamin D3 and C (ascorbate; as a control variable) in blood samples collected at W1 and W5. Vitamin D insufficiency (<30 ng/mL) was common at W1 (42%) and W5 (46%), and rates of clinically significant depressive symptoms (CES-D≥16) were 34–42% at W1–W5. Lower W1 vitamin D3 predicted clinically significant depressive symptoms across W1–W5 ( β =−0.20, p <0.05), controlling for season, BMI, race/ethnicity, diet, exercise, and time outside. There was some evidence that lower levels of depressive symptoms in Fall participants (vs. Winter and Spring) were explained by their higher levels of vitamin D3 . W1 depressive symptoms did not predict change in vitamin D3 levels from W1 to W5. Findings are consistent with a temporal association between low levels of vitamin D and clinically meaningful depressive symptoms. The preventive value of supplementation should be tested further. Highlights: Depressive symptoms and vitamin D were measured in 185 healthy women across 4 weeks. Significant symptoms and vitamin D insufficiency were common, and differed by season. Initially low vitamin D levels were associated with clinically significant depressive symptoms across follow-up. Between-subjects differences in depression by season were partially explained by seasonal changes in vitamin D. Racial-ethnic differences in depression were partially explained by group differences in vitamin D levels.